FACING TRANSLATION ERRORS AT INTERNATIONAL ORGANIZATIONS: WHAT CORRIGENDA REVEAL ABOUT CORRECTION PROCESSES AND THEIR IMPLICATIONS FOR TRANSLATION QUALITY - Prieto Ramos, Fernando (Comparative Legilinguistics, 2020)
Corrigenda issued by international organizations provide a most relevant source for the analysis of translation errors and what they reveal about institutional translation quality control and correction processes. This study examines corrigenda published in three settings (the European Union institutions involved in law-making, the United Nations and the World Trade Organization) in three years over a decade: 2005, 2010 and 2015. It reviews the procedures used to introduce translation corrections in these institutions before presenting the results of the quantitative and qualitative analysis of translation-triggered corrigenda in two target languages, French and Spanish, per setting, year, genre, error type and severity. A distinction is made between content reformulation corrections and minor formal corrections for the comparison of diachronic changes and semantic impact levels of corrected errors between the institutions considered. The findings confirm that minor formal errors may have meaning-distorting effects that are as serious as content reformulation errors; when this is not the case, they rarely trigger single-correction corrigenda. The UN recourse to “reissues for technical reasons” for translation corrections and the growing number of corrigenda to EU legal acts and their implications for translation quality assurance and legal certainty are further contextualized and discussed drawing on both corpus analysis and consultations with institutional informants.